Associations between poor oral health and reinjuries in male elite soccer players: a cross-sectional self-report study - Solleveld, H.; Goedhart, A.; Vanden Bossche, L. (BMC Sports Science, Medicine and Rehabilitation, 2015)
Background Although it is well known that oral pathogens can enter the systemic circulation and cause disease, it is largely unknown if poor oral health increases the risk of sports injuries. The purpose of this study is to investigate the association between poor oral health and reinjuries in male elite soccer players, adjusted for psychosocial problems and player characteristics. Methods 184 Players in premier league soccer clubs and 31 elite, junior soccer players in the Netherlands, Belgium and England, were enrolled in a retrospective cross-sectional study. The Sports Injury Risk Indicator, a self assessed questionnaire, was used to obtain information on reinjuries, age and player position, oral health and psychosocial problems. The number of different types of oral health problems was used as an indicator of poor oral health. (SumDental, range 0-2: 0 = no oral health problems, 1 = one type of oral health problem and 2 = two or more types of oral health problems). Multivariable logistic regression was used to investigate whether SumDental was associated with reinjuries, after adjustment for psychosocial problems and player characteristics. Results 37% of the players reported no oral health problems, 43% reported one type of oral health problem and 20% reported two or more types of oral health problems. After full adjustment for age, player position and psychosocial problems (i.e. injury anxiety, psychophysical stress, unhealthy eating habits and dissatisfaction with trainer/team), poor oral health (SumDental) was positively associated with all kind of reinjuries whether analyzed as a continuous variable or as a categorical variable. The fully adjusted odds ratios for SumDental analyzed as a continuous variable were: in relation to repeated exercise-associated muscle cramps: 1.82 (95% confidence interval (CI): 1.07, 3.12), in relation to muscle or tendon reinjury 1.57 (95% CI: 1.01, 2.45) and in relation to multiple types of reinjury 1.88 (95% CI: 1.19, 2.97). Conclusion The results from this study justify a thorough examination of the effects of oral health problems on the injury risk of playing elite soccer.